PEREMPUAN AGRESIF DAN OPRESIFÂ DALAM ANTOLOGI CERPEN KOMPAS 2012:TINJAUAN PSIKOLOGI-GENDERAnas Ahmadi, M.Pd. Jurusan Bahasa dan Sastra Indonesia, Universitas Negeri Surabaya, anas_ahmadieni@yahoo.com (Lentera, Jurnal Studi Perempuan, 2014)
Abstract:  The  aim  of  the  research  is  to  describe  (1)  aggressive  women  and  (2) oppressive  women  in  short  storie’s  anthology  Dari  Selawat  Dedaunan  sampai Kunang-kunang di Langit Jakarta (2012) published by  Kompas.  It will be analysed through gender-psychology theory. This research is qualitative research. The source of  the  data  is  short  stories’  anthology  entitled  Dari  selawat  dedaunan  sampai Kunang-kunang di Langit Jakarta  published by  Kompas in 2012. The result of  the analysis  shows  that  the  aggression  is  strongly  captured  in  the  short  story  entitled “Perempuan Tua dalam Kepala”. The types of aggression occur is soft aggression. While  the  story  that  strongly  captured  oppressive  woman  appear  in  short  story entitled “Mar Beranak di Limas Isa”. The oppression refers to Maryam’s oppression that is destined to have a son instead of a daughter. Keywords: soft aggression, oppressive, son